A low complexity RF based sensor array for lung disease detection using inkjet printing. Issue 4 (28th October 2018) - Tayyab, Muhammad; Sharawi, Mohammad S.; Shamim, Atif; Al‐Sarkhi, Abdelsalam
Abstract: This article presents the design of a low complexity, low power, small‐sized, wearable, inkjet printed, cheap, and noninvasive radio frequency (RF) based sensor array for pulmonary edema and emphysema condition monitoring inside the patient chest. The RF sensor consists of 38 electrodes and 37 ports. The size of the sensor is 4 cm × 89.4 cm to cover the chest of an average adult. The sensor is optimized to operate at 60 MHz. The scattering coefficients S i1 are measured at each passive port and then the Least Squares (LS) method is used to form an equation for average dielectric constant estimation. The dielectric constant estimation method is used to detect the presence of water/air in human and porcine lungs. The average measured dielectric constants of normal human lung tissue, edema, and emphysema infected lungs are estimated with errors of 3.54%, 4.83%, and 4%, respectively. The porcine lung tissue‐mimicking phantom with proper electrical properties is formed using a water and salt (NaCl) mixture. To detect the different stages of pulmonary edema, 200 mL water balls are inserted in the inner layer of the chest model. The measured errors were 2.68%, 0.87%, 2.18%, and 2.8% for normal porcine lung, adding 6 water balls, adding 12 water balls, and adding 18 water balls, respectively.